2021
DOI: 10.3390/healthcare9091166
|View full text |Cite
|
Sign up to set email alerts
|

Sleep as a Priority: 24-Hour Movement Guidelines and Mental Health of Chinese College Students during the COVID-19 Pandemic

Abstract: Research on the combined role of 24-hour movement behaviors (sleep, sedentary behavior [SB], and physical activity) in adult mental health, though important, is in its infancy. In the context of Canadian 24-hour movement guidelines integrating quantitative recommendations for sleep, SB, and moderate-to-vigorous physical activity (MVPA), this study aimed to examine the associations between meeting guidelines and mental health among college students. The study used a cross-sectional sample of 1846 Chinese colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
2
12
1
Order By: Relevance
“…Follow-up prospective cohort studies are needed to further explore the dose–response relationship between the two. In addition, there are many factors that induce negative emotions (such as diet, sleep, home environment, smoking, and drinking) [ 42 , 53 ]. Our study design was a cross-sectional study design, so we only considered physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up prospective cohort studies are needed to further explore the dose–response relationship between the two. In addition, there are many factors that induce negative emotions (such as diet, sleep, home environment, smoking, and drinking) [ 42 , 53 ]. Our study design was a cross-sectional study design, so we only considered physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Social support was provided by government authorities [ 49 , 52 - 54 , 61 , 62 , 68 , 72 , 84 , 86 - 88 ]; university authorities [ 12 , 48 , 50 , 51 , 53 - 55 , 57 - 59 , 62 , 64 , 65 , 67 , 69 , 91 , 93 ]; students’ affairs counselors and teachers [ 54 , 75 , 83 - 85 , 87 , 93 ]; family members [ 52 , 54 , 57 , 83 , 94 ]; health care authorities and professionals [ 52 , 63 , 66 , 75 , 77 - 79 , 87 ]; researchers [ 70 , 85 ]; and media-, internet-, and smartphone-based interventions [ 26 , 53 , 55 , 56 , 60 , 71 , 73 , 75 , 77 , 80 , 81 ]. Positive coping strategies were adopted by undergraduate students themselves [ 52 , 82 , 83 , 85 , 86 , 89 , 92 , …”
Section: Resultsmentioning
confidence: 99%
“…A recent study mentioned positive coping strategies as intervention measures to help improve college students’ psychological well-being [ 2 ]. Some of the 49 included studies reported positive coping strategies, including regulating emotions effectively [ 52 , 85 ]; meeting the sleep, sedentary behavior, and moderate-to-vigorous physical activity guidelines [ 82 ]; developing optimistic attitudes [ 86 ]; adopting problem-focused and adaptive emotion-focused coping [ 89 ]; enhancing positive self-beliefs (eg, hope and self-efficacy) and physical and psychological exercises [ 92 ]; and managing stress through time management and regular exercise [ 93 ]. Moreover, undergraduate students need to provide mutual peer support and accessible care, because perceived peer support and care alleviated depressive symptoms and met young people’s psychological and emotional needs [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations